Comparison of the Effects of Treadmill and Overground Running on Respiratory and Leg Muscles Strength, and Dyspnea Level in in Individuals with Low Physical Activity Levels - Promsri, Umpira; Chaikhot, Dhissanuvach; Thiamklang, Rungfa; Sriboonpeng, Jitraporn; Chalermphong, Sawitree; Jongpattana, Pipattanapong (Journal of health and health management, 2025)
The objectives of this study were to compare the effects of treadmill and overground running on respiratory and leg muscles strength, and as well as the level of dyspnea score in sedentary persons. The participants were individuals with a sedentary lifestyle, aged 20-35 years, and with a body mass index (BMI) 18.5-22.9 kilograms per square meter. Each of the two groups consisted of twenty-five participants. The first group received treadmill running training, while the second group received overground running training. The running protocol involved exercising at 75-85% of maximum heart rate for 30 minutes, warm up 5 minutes, and cool down 5 minutes per day, 3 days per week, over a period of 6 weeks. The outcome measurements included respiratory and leg muscle strength, and dyspnea level assessed at baseline, and after 3 and 6 weeks of training. The results of this study showed that after 6 weeks of training, there were statistically significant difference between groups in maximum expiratory pressure (p = 0.001) and dyspnea level (p = 0.04). In conclusion, treadmill and overground running can improve respiratory and leg muscle strength, and dyspnea level after more than 3 weeks training. Moreover, overground running can improve expiratory muscle strength more effectively than treadmill running, while treadmill running reduce dyspnea more effectively than overground running after 6 weeks of training.